(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article reveals the theoretical foundations of monitoring and analyzing educational activities in preschool educational organizations. Ensuring the quality of education is determined by the use of observation and analysis methods. According to the researcher’s theory, the scientific foundations of analyzing educational activities are revealed.